Smuggling, stealing, selling, shooting and safe-guarding a Huguenot library in Dublin, 1707–2024 - McElligott, Jason (The Huguenot Society journal, 2024)
This article examines the important personal library of the Huguenot refugee Élie Bouhéreau (1643-1719). The collection entered Marsh’s Library in Dublin in 1707 and remains in the Reading Room in which it was originally placed. Visitors to Marsh’s Library have often been told that the collection survives intact in its original form on the shelves. However, around 10 per cent of the initial donation of 2,057 volumes has been lost through theft, war damage, and a sale of ‘duplicates’ in 1833. This article discusses what is missing from Bouhéreau’s library and what these lost items tell us about the nature and scope of the original collection. It concludes with a discussion of the most pressing current threat to these books: climate change.